Avaliação da esporulação de Bionectria ochroleuca em diferentes meios de culturas - Chagas, Haroldo Antunes [UNESP]; Rosa, Daniel Dias [UNESP]; Basseto, Marco Antonio [UNESP]; Zanotto, Mauricio Dutra [UNESP]; Furtado, Edson Luiz [UNESP] (My University, 2010)
The biological control of the plants diseases, caused by fungi, is carried out using others organisms (predator, parasite or pathogen). Among the possible agents of biocontrol, a fungus has been highlighting as promising and it is known as Clonostachys rosea, asexual form of Bionectria ochroleuca. For that, it is necessary the in vitro production of spores of this fungus. In this study were tested several culture media to select those with better conidia production. The study was conducted at Plant Protection Division, in the Plant Production Department, FCA - UNESP, Botucatu campus, São Paulo state, Brazil. We used the isolated CCR64 (EMBRAPA-CNPMA). The means of crops were: BDA; Oats-Agar; Mazeina-Agar; Rice-Agar; V8-5%; V8-10%; V8-20%; TJ-5%; TJ-10, TJ-20%. The sporulation of the fungus in different culture media was estimated at 8° days after of the incubation. The data were analyzed using method of comparing averages, using the Tukey test, at 5% probability, and the data processed, using (X +1)0.5 transformation. All culture media tested were able to produce conidia. It was found that the best culture media for production of conidia of Bionectria ochroleuca is the TJ-5%, followed by TJ-20%, with an sporulation average of 3,5×106 conidia/ml.
Evaluation of the Bionectria ochroleuca sporulation in different culture media
Keywords: Biological control; Inoculant; Multiplication